Permutation Monotone Functions of Random Vectors with Applications in Financial and Actuarial Risk Management. (March 2015) - Li, Xiaohu; You, Yinping
Abstract : In this paper we develop two permutation theorems on argument increasing functions of a multivariate random vector and a real parameter vector. We use the unified approach of our two theorems to provide some important theoretical results on the capital allocation in actuarial science, the deductible and upper limit allocations in insurance policy, and portfolio allocation in financial engineering. Our results successfully improve or extend the corresponding works in the literature.